2015
DOI: 10.1002/jat.3209
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agent triclosan is a proton ionophore uncoupler of mitochondria in living rat and human mast cells and in primary human keratinocytes

Abstract: Triclosan (TCS) is an antimicrobial used widely in hospitals and personal care products, at ~10 mM. Human skin efficiently absorbs TCS. Mast cells are ubiquitous key players both in physiological processes and in disease, including asthma, cancer, and autism. We previously showed that non-cytotoxic levels of TCS inhibit degranulation, the release of histamine and other mediators, from rat mast cells (RBL-2H3), and in this study we replicate this finding in human (HMC-1.2) mast cells. Our investigation into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 85 publications
7
95
0
2
Order By: Relevance
“…Hits belonged to three main pharmacological classes (Figure 3F), anti-psychotics, antidepressants, and antihypertensives, all of which are consistently represented in small molecule libraries (Attene-Ramos et al, 2015; Gohil et al, 2010; Stavrovskaya et al, 2004). The majority of hits have been shown to uncouple mt-Δψ (e.g., carvedilol, triclosan, sertraline, and hexachlorophene) (Cammer and Moore, 1972; Oliveira et al, 2000; Weatherly et al, 2016), to induce mitochondrial swelling (e.g., meclomen and benzbromarone) (Tatematsu et al, 2016), and to impair ETC and OXPHOS (e.g., miconazol, tamoxifen, trifluoperazine, and mefloquine) (Cheah and Waring, 1983; Dickinson, 1977; Gohil et al, 2010; Tuquet et al, 2000). The remaining compounds included a monoamine transporter inhibitor (indatraline), two plasma membrane voltage-gated Ca 2+ channel blockers (amlodipine and nicardipine), and one 5-HT receptor agonist (tegaserod).…”
Section: Resultsmentioning
confidence: 99%
“…Hits belonged to three main pharmacological classes (Figure 3F), anti-psychotics, antidepressants, and antihypertensives, all of which are consistently represented in small molecule libraries (Attene-Ramos et al, 2015; Gohil et al, 2010; Stavrovskaya et al, 2004). The majority of hits have been shown to uncouple mt-Δψ (e.g., carvedilol, triclosan, sertraline, and hexachlorophene) (Cammer and Moore, 1972; Oliveira et al, 2000; Weatherly et al, 2016), to induce mitochondrial swelling (e.g., meclomen and benzbromarone) (Tatematsu et al, 2016), and to impair ETC and OXPHOS (e.g., miconazol, tamoxifen, trifluoperazine, and mefloquine) (Cheah and Waring, 1983; Dickinson, 1977; Gohil et al, 2010; Tuquet et al, 2000). The remaining compounds included a monoamine transporter inhibitor (indatraline), two plasma membrane voltage-gated Ca 2+ channel blockers (amlodipine and nicardipine), and one 5-HT receptor agonist (tegaserod).…”
Section: Resultsmentioning
confidence: 99%
“…Multiplying this result by the factors noted above, (1 mg cell/0.2 mg protein) and (cell/3.5×10 −6 mg), yields approximately 2.8 nmol of TCS is absorbed per mg of mammalian protein within the cells. Thus, approximately 2.8 nmol TCS exposure/mg cellular protein induced mitotoxicity in rat basophilic leukemia (RBL) mast cells (Weatherly et al 2016). Specifically using primary human keratinocytes, a significant decrease was noted in mitochondrial ATP production due to an exposure of 3 μM TCS (Weatherly et al 2016), which corresponds to approximately 0.8 nmol/mg protein .…”
Section: Triclosan Exposure Levels In Humansmentioning
confidence: 99%
“…Thus, approximately 2.8 nmol TCS exposure/mg cellular protein induced mitotoxicity in rat basophilic leukemia (RBL) mast cells (Weatherly et al 2016). Specifically using primary human keratinocytes, a significant decrease was noted in mitochondrial ATP production due to an exposure of 3 μM TCS (Weatherly et al 2016), which corresponds to approximately 0.8 nmol/mg protein . These levels may be overestimates of the amount of TCS that permeates cells because absorption may be less than 10% of the total amount since 200 μl is a large volume compared to the volume of 100,000 cells.…”
Section: Triclosan Exposure Levels In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, perfluorooctanoate (PFOA) and perfluorodecanoic acid (PFDA) elevate mitochondrial state 4 respiration and reduce state 3 respiration in isolated rat liver mitochondria (Keller et al, 1992; Langley, 1990) and are frequently detected in WWTP effluent. Finally, the general-use antimicrobial agent triclosan is a component of numerous personal care products and is a potent mitochondrial uncoupler in rat and human mast cells, primary human keratinocytes (Weatherly et al, 2016), and in 24-hour post-fertilization zebrafish embryos (Shim et al, 2016). Although the aforementioned mitochondrial effects were mostly described in mammalian laboratory models, a recent study of 12 diverse fish species demonstrated that 65–86% of human drug targets were evolutionarily conserved in the studied fish species, suggesting that the mechanisms of action of many CECs may share commonalities with fish (Brown et al, 2014).…”
Section: Introductionmentioning
confidence: 99%